Face threat sensitivity in distributive negotiations: Effects on negotiator self-esteem and demands - Tuncel, Ece; Kong, Dejun Tony; McLean Parks, Judi; van Kleef, Gerben A. (Organizational Behavior and Human Decision Processes, 2020)
Highlights • Face threat sensitivity (FTS) is reactive sensitivity to threats to self-image.• Counterpart competitiveness reduces high FTS negotiators’ global self-esteem (GSE).• Counterpart competitiveness reduces high FTS negotiators' performance self-esteem (PSE).• High FTS negotiators’ reduced GSE and PSE lead them to make lower demands.